2013
DOI: 10.1016/j.biomaterials.2013.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cellular uptake of GFP via unfolded supercharged protein tags

Abstract: a b s t r a c tOne of the barriers to the development of protein therapeutics is effective delivery to mammalian cells. The proteins must maintain a careful balance of polar moieties to enable administration and distribution and hydrophobic character to minimize cell toxicity. Numerous strategies have been applied to this end, from appending additional cationic peptides to supercharging the protein itself, sometimes with limited success. Here we present a strategy that combines these methods, by equipping a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…After exposure of the cells to GFP, fluorescence signals were not detected inside the cell body. This finding is in line with the results of Pesce et al [ 31 ], who did not observe cell-associated fluorescence after incubation of A549 cells with GFP for 24 h. The lack of cell-associated GFP signals might be due to the fact that GFP is not internalised by the cells. Alternatively, GFP fluorescence might be quenched by the low pH value present in endocytic vesicles or lysosomes or degraded by proteolytic enzymes.…”
Section: Resultssupporting
confidence: 92%
“…After exposure of the cells to GFP, fluorescence signals were not detected inside the cell body. This finding is in line with the results of Pesce et al [ 31 ], who did not observe cell-associated fluorescence after incubation of A549 cells with GFP for 24 h. The lack of cell-associated GFP signals might be due to the fact that GFP is not internalised by the cells. Alternatively, GFP fluorescence might be quenched by the low pH value present in endocytic vesicles or lysosomes or degraded by proteolytic enzymes.…”
Section: Resultssupporting
confidence: 92%
“…We investigated GFPs fused to unfolded supercharged polypeptide chains. 27,28 These genetically engineered tags consist mainly of the pentapeptide repeat [GVGXP] n , where X is either a positively charged lysine (K) residue or a negatively charged glutamic acid (E). 29 These motifs were multimerized to exhibit 36 charged amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly generic is the fusion of a folded cationic supercharged protein to another protein to enhance cell uptake. The same holds true for fusing supercharged unstructured polypeptides to a target protein to achieve high yields of internalization: Pesce et al reported a new strategy to enhance the cellular uptake of exogenous proteins with SUP tails . The best uptake was observed with GFP‐K72 fusion, containing 72 Lys residues per tail.…”
Section: Applications Of Supercharged Unstructured Polypeptides In Thmentioning
confidence: 97%
“…All these features are far beyond what is possible with conventional polyelectrolyte polymers. Supercharging proteins and polypeptides thus provides materials with exciting properties such as hyper‐temperature resistance and the ability of overcoming biological barriers in vivo . Moreover, these highly charged structures allow the assembly of bioliquids, organelle‐like condensed matter architectures, artificial biological nanocontainers, and interfacial coatings among many others.…”
Section: Introductionmentioning
confidence: 99%